Effects of grazing and feedlot finishing duration on the performance of three beef cattle genotypes in Uganda - Asizua, Denis; Mpairwe, Denis; Kabi, Fred; Mutetikka, David; Hvelplund, Torben; Weisbjerg, Martin Riis; Madsend, Jørgen (Livestock Science, 2017)
Beef production in Uganda is progressing from the traditional pastoral practices to sedentary semi-intensive systems. Consequently, farmers are continuously crossbreeding the indigenous cattle with exotic genotypes to improve meat yield. This study was conducted on-farm to evaluate the effects of feeding systems and feeding durations on performance of three locally available genotypes. A 2×3×3 factorial experiment was used to randomly allot 108 young bulls (9–15 months old), 36 for each of the three genotypes; Ankole x Holstein Friesian (AXF) (175±22 kg), pure Boran (208±34 kg) and a composite genotype (212±35 kg). The bulls were allotted to two feeding systems and three finishing durations. The feeding systems comprised sole grazing as the control where animals only grazed natural pastures and feedlot finishing where animals were fed a locally formulated total mixed ration containing 200 maize stover, 300 maize bran, 447 brewers’ spent grain, 50 molasses and 3 salt (NaCl) as g/kg on dry matter (DM) basis. The three durations were 60, 90 and 120 days excluding 14 days of adaptation period. Data was collected on feed intake, growth, slaughter and carcass characteristics. The Boran consumed less DM per kg of body weight gain than the AXF and composite. Feed conversion ratio (kg DM/kg body weight gain) ranged between 6.3±0.6 to 8.2±1.5 at the feedlot and 11.1± 4.1 to 17±4.0 for all genotypes and all durations. Growth and slaughter characteristics did not vary (P>0.05) between genotypes. However, carcass quality grade scores were higher (P<0.05) in the pure Boran and the composite genotypes than in the AXF crossbreds at 120 days of finishing. Average daily live weight gain (ADG) for all genotypes was approximately twice under feedlot finishing compared to sole grazing while hot carcass weight under feedlot was only higher than that of sole grazing by 30 kg in AXF, 37 kg in Boran and 45 kg in composite genotype at 120 days of finishing. Hot carcass weight and dressing percentages were similar (P> 0.05) between genotypes irrespective of the feeding system for all durations but hot carcass weight was higher (P<0.05) at the feedlot for all durations. Therefore, intensification through feedlotting is a viable option for improving beef production. However, understanding the appropriate levels of crossing between genotypes is needed to achieve the desired improvement in productivity from crossbreds.
Keywords: Beef; Production systems; Grazing Tropical cattle